2014
DOI: 10.1007/s11242-014-0427-z
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Averaged Equations with Variable Density for $$\hbox {CO}_2$$ CO 2 Flow in Porous Media

Abstract: Carbon capture and storage has been proposed as a viable option to reduce CO 2 emissions. Geological storage of CO 2 where the gas is injected into geological formations for practically indefinite storage, is an integral part of this strategy. Mathematical models and numerical simulations are important tools to better understand the processes taking place underground during and after injection. Due to the very large spatial and temporal scales involved, commercial 3D-based simulators for the petroleum industry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Early methods assumed a sharp interface between CO 2 and the resident brine and were successfully applied to study long-term CO 2 migration in the large-scale Utsira [23] and Johansen [24] aquifers. Since then, the VE formulation has been extended to include many relevant physical effects, such as compressibility [25], convective dissolution [26], capillary fringe [27], smallscale caprock topography variations [28][29][30], as well as various hysteretic effects [31,32]. Presently, VE formulations can be used to efficiently simulate CO 2 migration and resolve the delicate balances governing structural, residual, and solubility trapping over thousand of years.…”
Section: Simulating Co Migration In Large-scale Aquifer Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Early methods assumed a sharp interface between CO 2 and the resident brine and were successfully applied to study long-term CO 2 migration in the large-scale Utsira [23] and Johansen [24] aquifers. Since then, the VE formulation has been extended to include many relevant physical effects, such as compressibility [25], convective dissolution [26], capillary fringe [27], smallscale caprock topography variations [28][29][30], as well as various hysteretic effects [31,32]. Presently, VE formulations can be used to efficiently simulate CO 2 migration and resolve the delicate balances governing structural, residual, and solubility trapping over thousand of years.…”
Section: Simulating Co Migration In Large-scale Aquifer Systemsmentioning
confidence: 99%
“…Likewise, the model equations include rock compressibility but disregard fluid compressibility. The effect of variable density in vertical-equilibrium models was investigated by Andersen et al [25], who concluded that for the vast majority of long-term, large-scale storage systems it is sufficient to account for CO 2 density variations only in the lateral direction (i.e., a semi-compressible model). Both fully compressible and semi-compressible models have been implemented in MRST, but for brevity we herein disregard fluid compressibility when discussing how to derive expressions for effective properties by vertical integration.…”
Section: Basic Ve Models With a Capillary Fringementioning
confidence: 99%
See 2 more Smart Citations
“…Early studies focused on VE models with a sharpinterface assumption [24][25][26], and models that only account for the basic effects of buoyant migration were successfully used to simulate long-term migration in the Utsira [27] and Johansen [28] aquifers. Later, the class of VE models has been extended to incorporate most of the flow effects that are pertinent to large-scale migration, including compressibility [29], convective dissolution [30,31], capillary fringe [32], small-scale caprock topography variations [33][34][35], various hysteretic effects [36][37][38], multiple geological layers [39,40], and heat transfer [41]. In particular, several studies show that vertical equilibrium simulations compare well with 3D simulators on case studies of the Johansen aquifer [42] and the 9 th layer of the Sleipner injection [27,43].…”
Section: Introductionmentioning
confidence: 99%